URBANIZATION IN BANGLADESH: EMERGING CHALLENGES AND THE WAY FORWARD - Lipi, Afroza Islam; Hasan, Nazmul (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
Urbanization is a natural process of the population shift from rural to urban territories. More specifically, urbanization is a process of migration of population from rural to urban areas as well as the transformation of society where the rural agricultural economy is being transformed to advance the industrial economy.  A major change to be witnessed in Bangladesh over the last few decades is the rapid spread of urbanization. Multiple driving factors paved the way for spreading the rapid growth of urbanization in Bangladesh. If this spread is not effectively managed, emerging challenges like spatial imbalance, environmental challenges, weak policy framework, challenges of sustainable cities, urban poverty, urban health issues, etc are likely to grow. This study aims at exploring the emerging challenges of urbanization in Bangladesh. It also explores the way forward to face the emerging challenges. This study has been conducted depending on qualitative and descriptive analysis. It is mainly based on secondary data. Available books, journals, documents, newspapers, data, reports, and magazine articles are reviewed in detail as a secondary source. In the findings of the study, the rapid growth trend has been critically examined. Besides emerging challenges of urbanization in Bangladesh have been identified. Finally, some recommendations have been put forward to overcome the emerging challenges of urbanization in Bangladesh.  JEL Classification Codes: D8, O15, O18.